The Effect of Halal Awareness and Perceived Value on Purchasing Decisions for Charm Brand Halal Sanitary Napkins with Purchase Intention as an Intervening Variable - Nurdiasari, Aisyah Putri; Fikriyah, Khusnul (Jurnal Iqtisaduna, 2025)
This study aims to analyze the influence of halal awareness and perceived value on purchase decisions of Charm halal-certified sanitary pads, with purchase intention as a mediating variable. Using a quantitative approach, data were collected from 187 respondents through a questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that halal awareness significantly influences purchase intention but does not directly affect purchase decisions. In contrast, perceived value significantly influences both purchase intention and purchase decisions. Furthermore, purchase intention mediates the relationship between perceived value and purchase decisions, but does not mediate the relationship between halal awareness and purchase decisions. This study highlights the relevance of perceived value in marketing non-food halal products. This topic has received limited attention in previous literature and offers practical insights for enhancing marketing strategies and supporting the growth of the halal industry in Indonesia.